Foreign direct investment in South Asia: Policy, trends, impact and determinants - Pravakar Sahoo (Asian Development Bank Institute (ADBI), 2006)
All five South Asian countries (India, Pakistan, Bangladesh, Sri Lanka and Nepal) have been following consistent economic reform policy measures emphasizing the market economy and aimed at integrating their economies with the rest of the world. Consequently, all except Pakistan have experienced higher economic growth and an improvement in most macro economic indicators both in the domestic and external sector. Indeed, the South Asian region has been one of the fastest growing regions in the world in recent years. Overall, the FDI environment has undergone a sea change in South Asian countries during the 1990s, and more so in recent years. With their liberalized approach to FDI and constant changes in improving the FDI policy framework, it is certain that South Asia has become an important destination for investment. Thus, one can conclude that there has been a positive change in policies with regard to FDI with efforts directed more towards bilateral trade agreements and providing investment incentives to foreign investors in all South Asian countries. However, there are still procedural delays, reserved industries where foreign investors are not allowed to invest and ceilings in many industries/sectors in each of these countries. Accelerating the economic reform process and making their economies politically stable and free from internal conflict would go a long way toward making South Asia an attractive destination for FDI. The basic indicators, including infrastructure, show that all five south Asian countries lack adequate infrastructure facilities and governance. Thus, more effective public investment on economic and social infrastructure, along with stable economic policies to create an enabling environment, would attract more foreign direct investment. Analyses of FDI flows to south Asian countries reveal that there has been an increasing trend of FDI into South Asian countries. However, apart from India, the share as well as the absolute volume of FDI inflow to these countries is negligible. FDI in South Asia is mostly concentrated in manufacturing and services. An analysis of FDI inflows to different sectors shows that FDI is largely domestic market oriented in India and Pakistan, whereas it is concentrated in a few export-oriented industries in Sri Lanka and Bangladesh. The results of FDI impact on growth show that FDI has a positive and significant impact on growth for four south Asian countries. Other significant factors that contribute to growth are exports, gross domestic capital formation and infrastructure. Therefore South Asian countries need to improve their domestic investment, exports and infrastructure facilities, along with more foreign investment, to achieve higher growth. Further, FDI has a positive impact on export growth through its positive spillovers for South Asian countries. Though FDI does not affect domestic investment in the current period, it has a positive and significant impact affect over time through dynamic effects. The results of a panel cointegration estimation reveal that FDI and all its potential determinants have a long run equilibrium relationship. Major determinants of FDI in South Asia are market size, labor force growth, infrastructure index and trade openness. Overall, South Asian countries need to maintain growth momentum to improve the market size, frame policies for better use of the abundant labor force, improve infrastructure facilities and follow more open trade policies to attract increased FDI.
Keywords: 330